Membangun Kesadaran Masyarakat tentang Gizi Seimbang sebagai Upaya Mengatasi Stunting di Desa Cangguek Kecamatan Tanah Pasir Kabupaten Aceh Utara - Quranayati Quranayati; Srie Wahyuni; Rouzatul Nafisah; Putri Ayu Ariska; Meli Sahara (Pusat Riset dan Inovasi Nasional, 2026)
Toddler age is often called the golden period because during this period brain nerve development occurs, especially myelination, as well as a critical period. The golden period can be achieved if toddlers' nutritional needs are optimally met. On the other hand, if babies and toddlers do not get the food they need, the golden period will change into a critical period, thus disrupting their growth and development. The level of education of parents will affect the health and well-being of children, because this is inseparable from the nutritional status of children. Mothers with a high level of education will have a clearer opportunity to absorb information compared to mothers with less or no education. With a good level of education, it is hoped that a mother will be willing and able to behave well in order to improve her child's nutritional status. This Community Service activity aims to provide health education on balanced nutrition to reduce stunting in the community, especially mothers with toddlers in Desa Cangguk, Kecamatan Tanah Pasir, Kabupaten Aceh Utara. This activity used a participatory approach involving lecturers, students, health workers, and the community. The results showed an increase in public understanding and awareness of stunting prevention. It is hoped that this activity will raise public awareness about balanced nutrition for children